Efek Olahraga terhadap Kejadian Dismenor Primer pada Siswi Kelas X SMA Negeri 78 Jakarta Barat - Nauri Anggita Temesvari; Loli Adriani; Witri Zuama Qomarania (Media Kesehatan Masyarakat Indonesia, 2019)
The prevalence of dysmenorrhea is mostly experienced by teenagers. Study showed that woman who didexercise had less proportion to feel dysmenorrhea. For that reason, this research purpose to analyze effect exerciseon primary dysmenorrhea among student grade 10th in SMA Negeri 78 Jakarta Barat, which family historicalmenstruation pain, menstruation period, menarche, stress, coffee consumption, smoke exposure, and alcoholconsumption was controlled. To reach that purpose, the research used analysis method with case control study. Theminimum sample size used in this case-control study was calculated based on the hypothesis testing of differentproportions so that we obtained a total sample of cases and controls of 84 female students. Bivariate analysisshowed alcohol consumption and exercise had related to primary dysmenorrhea (p-value < 0.05). After controlledsome variables, multivariate analysis showed exercise had effected to primary dysmenorrhea with p-value 0.043and OR 1.937 (95% CI: 1.124 – 3.913). The result showed lack of exercise had a chance 1.937 times to feelprimary dysmenorrhea.